2010
DOI: 10.1159/000313368
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Lipid and Carbohydrate Metabolism in Patients with Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency

Abstract: Background: Classic 21-hydroxylase deficiency (21HD) presents some traits of the metabolic syndrome. Aim: To characterize discrete alterations of lipid and carbohydrate metabolism in children and young adults with classic 21HD, which could predict early atherogenesis. Patients and Methods: Twenty-seven Caucasian patients with classic 21HD (4–31 years); 27 sex-, age- and BMI-matched controls. Clinical parameters, hormonal status and genotype were assessed in all patients. Lipid parameters, including relative (%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 74 publications
1
30
2
1
Order By: Relevance
“…Several studies have revealed unfavorable trends in the cardiovascular status and metabolic risk of adults with CAH [11,15,22,23,24]; however, the data on children and adolescents with CAH are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed unfavorable trends in the cardiovascular status and metabolic risk of adults with CAH [11,15,22,23,24]; however, the data on children and adolescents with CAH are limited.…”
Section: Discussionmentioning
confidence: 99%
“…In young CAH patients, increased obesity prevalence [14], lipid levels [15,16] and insulin resistance [17] compared with controls have been reported. However, these previous studies were inconclusive because they included patients with both the classical and nonclassical forms of CAH who were receiving a mixture of GC regimes along with different approaches for hormonal control during the course of CAH management.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obese adults with classic CAH had similar lipid profiles to patients with normal BMI [33]. Decreased HDL levels and increased small-dense LDL were found in 27 children and young adults [49]. A larger and more homogeneous cohort of 61 females showed an even higher HDL/LDL ratio in CAH women older than 30 years (n = 34) compared to controls [39].…”
Section: Cardiovascular and Metabolic Healthmentioning
confidence: 99%
“…Além disso, essas mulheres têm maior prevalência de obesidade, resistência à insulina, dislipidemia e hipertensão (24). Esses fatores em conjunto traduzem a síndrome metabólica, com consequente risco cardiovascular aumentado (7,59,60). No entanto, ainda não foi demonstrada maior morbidade ou mortalidade cardiovascular ou risco de diabetes tipo 2 nessas mulheres (9).…”
Section: Outras Consideraçõesunclassified